Drawing on Religion in the Desistance Process: Paying Attention to Race and Ethnicity - Stansfield, Richard (Criminal justice and behavior, 2017)
Religion is important in the lives of many ex-offenders. This study uses data from the Pathways to Desistance Study data set to examine the impact of religiosity on criminal desistance and drug use among delinquent White, Black, and Hispanic youth. Results from mixed-effects longitudinal analyses revealed that religiosity was a significant predictor of lower criminal offending and substance use for White youth postconviction, controlling for changes in employment, social support, and delinquent peer association. Although religiosity was associated with lower substance use among Black youth, it was not associated with lower criminal offending among Black or Hispanic youth. We discuss the implications of our findings for research and policy, particularly the need for resources.